Muslim di Amerika Utara dan Amerika Latin - Satria Setiawan; Muhammad Affan (Madaniyah, 2019)
So far, Islam is more widely represented in Muslim-majority areas. Thus, Muslim minority areas are often overlooked. In fact, the existence of Muslims in a region, although the minority is a representation of the spread of Islam and the spread of Muslims around the world. Therefore, the study and discussion of Muslim minorities in a region becomes urgent. Based on the urgency, the following article will describe the condition of Muslim minorities in the region of North America and Latin America. This article aims to provide information that illustrates the problems faced by Muslim minorities in the two regions. This information is expected to foster a better caring spirit for Muslims.